THE ROLE OF THE VAVILOV INSTITUTE OF PLANT INDUSTRY IN THE INITIATION AND DEVELOPMENT OF NEW TRENDS IN WINTER RYE BREEDING IN RUSSIA - V. D. Kobyliansky; O. V. Solodukhina (Труды по прикладной ботанике, генетике и селекции, 2018)
Scientific investigations conducted at VIR during 1960-2014 to identify sources of new promising and economically useful traits in rye resulted in the development of genetic donors of such traits capable of increasing breeders’ work efficiency. These results helped to initiate the development of new priority trends in winter rye breeding, such as breeding of heterosis hybrid cultivars, semi-dwarf non-lodging cultivars, cultivars resistant to fungal diseases, semi-dwarf forms with higher productivity on the basis of plant photosynthesis potential optimization, and rye cultivars with low pentosan content for universal utilization.